Sistem Pendukung Keputusan Penerimaan Karyawan Baru Menggunakan Kombinasi Metode Analytical Hierarchy Process dan Weighted Product - Abdullah, Tariq Roja; Rosyda, Miftahurrahma (Journal of Information System Research (JOSH), 2024)
Employees are valuable to a company, so hiring the right ones is crucial. However, "Kenapa Creative" startup struggles with recruiting, as 179 applicants overwhelm their staff. Manual data management makes it hard to get the best results. To tackle this, a Decision Support System (DSS) is developed. The goal of this research is to create an employee recruitment DSS to help startup managers make hiring decisions more easily. It begins with collecting recruitment-related data through interviews and literature review. System design starts from activity diagrams to application with the Analytical Hierarchy Process (AHP) method for prioritizing criteria and sub-criteria, while the Weighted Product (WP) method is used for alternative ranking. AHP is considered capable of decomposing complex problems using hierarchies, making a problem more structured and systematic. WP is deemed to have simple complexity, making computation time faster and addressing recruitment problems requiring quick selection. DSS testing uses Black Box, Usability, SPK validity, and Expert Judgment methods. The research results in an employee recruitment DSS. The system can obtain the best candidate to be accepted. The system features work according to black box testing. SUS testing yields scores of 78.5 from the applicant side and 84.5 from the admin side, categorizing the system as Acceptable. SPK validity testing results in an 80% percentage from the comparison between manual calculations and the system. Expert Judgment testing shows that the system produces alternative rankings consistent with expert views.